Penerapan Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Analitis Siswa Kelas X MIA 6 SMA MTA Surakarta Tahun Pelajaran 2013/2014 pada Materi Pencemaran Lingkungan - Ulya Granit Pramudita; Riezky Maya Probosari; Sri Widoretno (Universitas Sebelas Maret, 2014)
This study was aimed to improve the students’ analytical thinking ability of biology subject in X MIA 6 of SMA MTA Surakarta academic year 2013/2014 through the implementation of Problem Based Learning. This research is a class action research which consists of three cycles. Each cycle contains planning, implementing, observing and reflecting. The subject of this research is the students in X MIA 6 of SMA MTA Surakarta academic year 2013/2014. The data colecting techniques of this research are using observation, interview and documentation. The data validation of this research is using triangulation method. The data result of observation, interview and documentation are analyzed by using qualitative analysis which is done in three components, they are: data reduction, data presentation and drawing the conclusion or verification. The research procedure is using spiral method. The results show that students analytical thinking ability is increased in Pre-cycle, Cycle I, Cycle II and Cycle III. The average of students analytical thinking ability increase from 21,45 % to 47,51%. Identifying elements aspect increase from 22, 42% to 53, 33%. Grouping and describing elements in categories aspect increase from 23, 64% to 46, 67%. Describing process aspect increase from 21, 21% to 46, 06%. Interpreting simple series of data aspect increase from 20% to 49,09%. Expressing information in simple tables or graphs aspects increase from 20% to 42,42%. This research’s conclusion is the implementation of Problem Based Learning can improve analytical thinking ability of the student in X MIA 6 class at SMA SMA MTA Surakarta. Key Words: problem based learning, analytical thinking